Perbedaan individu anak terhadap pola asuh orangtua - Nabila Permata Yuri (JRTI (Jurnal Riset Tindakan Indonesia), 2017)
Individual differences make each parent have a different parenting pattern to their child. Individual differences concern about variations that occur, both variations on physical and psychological aspects. Parenting is the attitude of parents in interacting with their children is a picture used by parents to take care (care, maintain, or educate). How individual differences become the foundation for parents to give a pattern that can not be beat equally for all children. Hope this can be used as a reference.